The effectiveness of nearpod assisted digital daily assessment to improve the creative thinking abilities and metacognitive skills of science students - Bea Hana Siswati; Suratno Suratno; Slamet Hariyadi; Jekti Prihatin; Bevo Wahono; Amrina Rosyadah (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
This study delves into the pressing requirement for employing Nearpod-supported daily digital assessments to boost students' creative thinking abilities and metacognitive skills. This research aims to evaluate the effectiveness of using the Daily Assessment digital learning media assisted by Nearpod in improving junior high school biology science students' creative thinking abilities and metacognitive skills. This is a quasi-experimental research. The research participants consisted of two classes of science students at junior high school who were chosen randomly. The experimental class consisted of 27 students, while the control group consisted of 24 students. Data collection tools include validated tests of creative thinking abilities and metacognitive skills. Data were analyzed using descriptive and inferential statistical techniques using the ANCOVA test. The research results show that using the Daily Assessment digital learning media assisted by Nearpod significantly improves students' creative thinking abilities and metacognitive skills compared to conventional learning methods. Students demonstrate an increased capacity to generate new ideas, make connections between subtopics, and solve problems creatively. This research proves that the Daily Assessment digital learning media assisted by Nearpod effectively improves students' creative thinking abilities and metacognitive skills.Abstrak Studi ini menggali kebutuhan mendesak untuk menerapkan penilaian digital harian yang didukung Nearpod untuk meningkatkan kemampuan berpikir kreatif dan keterampilan metakognitif siswa. Penelitian ini bertujuan untuk mengevaluasi efektivitas penggunaan media pembelajaran digital Daily Assessment berbantuan Nearpod dalam meningkatkan kemampuan berpikir kreatif dan keterampilan metakognitif siswa sains biologi Sekolah Menengah Pertama (SMP). Ini adalah penelitian kuasi eksperimen. Partisipan penelitian terdiri dari dua kelas siswa sains di SMP yang dipilih secara acak. Kelas eksperimen terdiri dari 27 siswa, sementara kelompok kontrol terdiri dari 24 siswa. Alat pengumpulan data meliputi tes kemampuan berpikir kreatif dan keterampilan metakognitif yang telah divalidasi. Data dianalisis menggunakan teknik statistik deskriptif dan inferensial dengan menggunakan uji ancova. Hasil penelitian menunjukkan penggunaan media pembelajaran digital Daily Assessment berbantuan Nearpod secara signifikan meningkatkan kemampuan berpikir kreatif dan keterampilan metakognitif siswa dibandingkan metode pembelajaran konvensional. Siswa menunjukkan peningkatan dalam kapasitas mereka untuk menghasilkan ide-ide baru, menjalin hubungan antar subtopik, dan memecahkan masalah secara kreatif. Penelitian ini membuktikan media pembelajaran digital Daily Assessment berbantuan Nearpod efektif mening-katkan kemampuan berpikir kreatif dan keterampilan metakognitif siswa.